Elaboração de um plano de manutenção utilizando conceitos de manutenção produtiva total - Chiquito, Anderson (2018)
Maintenance is a relevant factor in the production processes, increasing the reliability, profitability and competitiveness in the market. The present work aims to develop the maintenance planning for a CNC equipment used the company X, active in the metal mechanic branch of the metropolitan region of Curitiba, for this was used of management tools and concepts of TPM (Total Productive Maintenance), proposing preventive maintenance actions consistent with the current situation of the company and training to promote Autonomous Maintenance. By applying the Pareto diagram it became possible to visualize the pilot equipment with 60% of the stop numbers between machines and 87% of the total time of machine stop, it is expected that from the implementation of the Autonomous Maintenance the company already reaches positive results that will help the company to maintain its future cash flow while remaining competitive in the long run.